How Can a Punch Knock You Out? - Hånell, Anders; Rostami, Elham (Frontiers in Neurology, 2020)
Several hypotheses have been put forth over time to explain how consciousness can be so rapidly lost, and then spontaneously regained, following mechanical head trauma. The knockout punch in boxing is a relatively homogenous form of traumatic brain injury and can thus be used to test the predictions of these hypotheses. While none of the hypotheses put forth can be considered fully verified, pore formation following stretching of the axonal cell membrane, mechanoporation, is a strong contender. We here argue that the theoretical foundation of mechanoporation can be strengthened by a comparison to the experimental method electroporation.